PENINGKATAN KETERAMPILAN TEST TOEIC BAGI SISWA/SISWI BERBASIS TEKNOLOGI DI SMKN 1 LABUHAN MARINGGAI, LAMPUNG TIMUR - Heri Kuswoyo; Ingatan Gulo; Almira Devita Putri; Ad. Dasa Erliani; Yogi Fajar Darmawan (EDUPEDIA Publisher, 2023)
The Test of English for International Communication (TOEIC) is a means of professional development for students at Vocational High Schools (SMK). SMK students are required to have skills in the field of communication in international languages so that they are able to guarantee the quality of their own future. The purpose of this Community Service activity (PKM) is to provide an understanding of the TOEIC test for students of SMKN 1 Labuhan Maringgai, East Lampung. This PKM activity uses several methods such as observation, questionnaires, interviews and documents. The results of this PKM show that the TOEIC skills of students at SMKN 1 Labuhan Maringgai have increased after participating in technology-based PKM activities.